Problems automating condition monitoring of modern systems of airfield Light - Дев'яткіна, С.С. (Proceedings of National Aviation University (archive), 2007)
Main problems of monitoring and diagnosis automation of aerodrome lights technical state in modern airfield lighting systems are formulated and analyzed.